Mining of frozen iron ore in northern Québec and Labrador - Garg, Om (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1979)
Mining exploration and production activities in the permafrost regions of Canada have increased rapidly over the last twenty years. This paper deals with the effects of permafrost on mining iron ore in the Schefferville area of Northern Québec and Labrador. Problems associated with drilling and blasting, digging and crushing, transportation and handling of frozen ore are briefly outlined. The three dimensional delineation of frozen ground is achieved by a combination of ground temperature measurements and geophysical techniques. Finally some of the studies that are planned to be undertaken in the Schefferville area are briefly mentioned.